An Environmental Community Approach to the Problem of Global Warming - Rozas O., Germán (Revista de Psicología, 2003)
Community Psychology has much to say about environmental topics. This article presents the very serious problem of Global Warming pointing out the consequence this phenomenon has on the human population. Causes are revised and an emphasis is laid on how human society itself provokes the warming of the planet through behaviors and life styles which incorporate a completely economical approximation to the environment. Other paradigms are reviewed which, in general, propose possible changes through generating the awareness that human beings are part of the ecosystem and for this reason nature should not be understood as a warehouse for food. Other lines of intervention are offered, from a community perspective, which could be undertaken in conceptual as well as operative dimensions.